2022
DOI: 10.1007/s11356-022-24846-0
|View full text |Cite
|
Sign up to set email alerts
|

Does economic policy uncertainty impact firms’ capital structure policy? Evidence from Western European economies

Abstract: This study specifically investigates the impact of economic policy uncertainty (EPU) on travel and leisure (TL) companies’ debt holdings policy. To the best of our knowledge, there is a momentous gap in exclusively conducting the impact of EPU on the debt holdings policy behavior of Western European firms operating in the TL sector and its sub-sectors, namely the airlines, gambling, hotels, recreational services, restaurants and bars, and travel and tourism. In this sector, external financing is strongly neede… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…We observed how much focus financial managers have on financial leverage and decisions regarding the use of internal funds or external sources and found that it has a negative relationship with Tobin's Q, which means the usage of internal funds is supportive as compared with debts. We lag Tobin's Q and MPPS variable by one period, following [45,46]. The following is the central equation in Model 4, the primary model for our upcoming empirical discussion.…”
Section: Findings Difference Points Citationsmentioning
confidence: 99%
“…We observed how much focus financial managers have on financial leverage and decisions regarding the use of internal funds or external sources and found that it has a negative relationship with Tobin's Q, which means the usage of internal funds is supportive as compared with debts. We lag Tobin's Q and MPPS variable by one period, following [45,46]. The following is the central equation in Model 4, the primary model for our upcoming empirical discussion.…”
Section: Findings Difference Points Citationsmentioning
confidence: 99%
“…These investigations have, however, mainly been performed within one industry or using simple industry dummies across industries. Studies have focused on the statistical and economic significance of estimated coefficients but not on the reasons for the difference in leverage, which goes beyond such an analysis, in cases where single industries have not been examined, such as construction (Ruckova and Skulanova 2022), tourism (Athari and Bahreini 2023), manufacturing (Sardo et al 2022), the financial sector (Boateng et al 2022), and the non-financial sector (Bazhair and Alshareef 2022;Khan et al 2023). On the contrary, Yang et al (2015) concluded that almost all the studies carried out in China regarding debt examinations do not recognize differences among business sectors.…”
Section: Resultsmentioning
confidence: 99%
“…Athari and Bahreini [ 67 ] investigated the effects of economic policy uncertainty on travel and leisure companies’ debts in western Europe. Economic policy uncertainty had adverse effects on travel and leisure companies’ debt level.…”
Section: Literature Review On the Application Of Granger Causalitymentioning
confidence: 99%